Towards a method compendium for the development of digitised products - findings from a case study. (2018) - Holler, Manuel; Herterich, Matthias; Dremel, Christian; Uebernickel, Falk; Brenner, Walter
The pervasive infiltration of digital technology into physical products brings both tremendous challenges and opportunities to original equipment manufacturers. With the goal to support the initial stages of the product lifecycle, this article introduces a method compendium for the development of digitised products. More precisely, the compendium suggests: 1) customer- and user-centric innovation methods; 2) agile and prototyping methods; 3) system and architecture modelling methods; 4) feedback- and data-driven methods; 5) service and business modelling methods. Methodically, we draw on secondary data from a longitudinal single-case study scrutinising the development of digitised trucks at a leading materials handling and intralogistics organisation. Bounded to the business-to-business context of industrial equipment manufacturing, we enrich product lifecycle management with methodological contributions valuable for academia and practice alike.